Depicting the Holocaust through Self-Reflexive Forms of Representation. An Interdisciplinary Perspective (KULT_online, 2018)
The debate concerning how to sufficiently depict the Holocaust has never lost its popularity. On the contrary, it continuously emerges in the context of new ways of representation and new media. The volume Notwendige Unzulänglichkeit (‘Necessary Inadequacy’), edited by Nina Heindl and Véronique Sina, is composed of eleven interdisciplinary, yet very coherent contributions. They aim at analyzing Holocaust portrayals in art, literature and new media through the lens of the tension between the need for a re-elaboration of the past and the inadequacy of grasping the Shoah in its totality. The authors focus on the self-reflexive charge of the new forms of representation that are not limited to conveying the Holocaust, but critically reflect on the conventions of traditional representations.